Sistem Temu Kembali Informasi dengan Pemeringkatan Metode Vector Space Model - Fathkul Amin (Dinamik, 2013)
The objective of designing  information retrieval system (IRS)   with Vector Space Model (VSM) Method is to facilitate users to search Indonesian documents. IRS Software is designed to provide search results with the optimum number of documents (low recall) and accuracy (high precision) with VSM method that users may get fast and accurate results. VSM method provides a different credit  for each  document  stored in  a  database which in turns  to determine  the  document most similar  to  the query, where  the documents with the highest credits are placed on the top of  the search results.   The evaluation of search results with IRS is conducted under recall and precision tests. This study  fascinatingly creates a  system which can preprocess  (tokenizing,  filtering, and stemming) within computation time of four minutes forty-one seconds.    Keywords: IRS, Vector Space Model, recall, precision